Short Communication: Landmark-based geometric morphometric analysis of wings to distinguish the sex of Aedes mosquito vectors in Thailand - TANAWAT CHAIPHONGPACHARA; SEDTHAPONG LAOJUN (Biodiversitas Journal of Biological Diversity, 2019)
Chaiphongpachara T, Laojun S. 2019. Short Communication: Landmark-based geometric morphometric analysis of wings to distinguish the sex of Aedes mosquito vectors in Thailand. Biodiversitas 20: 419-424. Aedes mosquitoes (Diptera: Culicidae) are medically important insects which are vectors of yellow fever, dengue fever, chikungunya, West Nile, and the Zika virus, emerging problems worldwide. Typically, male (non-vector) and female (vector) Aedes mosquitoes can easily be separated, however, the samples in the field is often incomplete, making it difficult to separate male and female mosquitoes. The goal of this research is to study the effectiveness of the landmark-based geometric morphometric technique to distinguish the sex of male and female Aedes mosquito vectors, including Ae. aegypti, Ae. albopictus, and Ae. scutellaris, in Thailand. Evaluation of wing size by centroid size analysis found that males and females are distinctly different; females are larger than males in three species of Aedes mosquito. The wing centroid size of Ae. aegypti and Ae. albopictus were very similar, however, Ae. scutellaris was smaller than in both other species. The wing shape between sexes was different in all groups of Aedes mosquitoes. The accuracy of the sex’s classification of Aedes vectors was quite high (more than > 80% from the cross-validated reclassification test). The results of this study prove that landmark-based geometric morphometric can distinguish sexes in Aedes vectors which can be used to solve problems in the field when it is necessary to distinguish the sexes of Aedes mosquitoes with damaged samples.